2008
DOI: 10.3748/wjg.14.5371
|View full text |Cite
|
Sign up to set email alerts
|

Satiety testing: Ready for the clinic?

Abstract: Drink tests are advocated as an inexpensive, noninvasive technique to assess gastric function in patients with a variety of upper digestive symptoms. Many patients with dyspeptic complaints wil l achieve satiation or develop symptoms at ingested volumes below those typically required to achieve these endpoints in controls. Substantial variation in test performance exists and a greater degree of standardization is required. Additionally, it remains unclear exactly what drink tests measure as correlations with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…2 Nutrient drink tests were developed as a symptom provocative technique for patients with dyspeptic complaints. 4 Male ingest greater volumes than female patients but there BMI. 4 Our study also showed similar results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Nutrient drink tests were developed as a symptom provocative technique for patients with dyspeptic complaints. 4 Male ingest greater volumes than female patients but there BMI. 4 Our study also showed similar results.…”
Section: Discussionmentioning
confidence: 99%
“…4 Male ingest greater volumes than female patients but there BMI. 4 Our study also showed similar results. But in FD patients, male and female ingested similar volume, it was because of impaired gastric accommodation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different nutrient drink tests based on various nutrient containing solutions, are performed with various drinking rates 1-3. Nutrient drink test developed by Mayo Clinic presents the simplest method among other tests 4. Subjects consume 120 mL of Ensure™ (Abbott Laboratories, Abbott Park, IL, USA), which contains 1.06 kcal/mL with 65% of carbohydrate, 20% of fat and 15% of protein, every 4 minutes until full 5.…”
Section: Performing Nutrient Drink Testsmentioning
confidence: 99%
“…Recently, good reproducibility of the drinking test has been shown [12]. In contrast, other investigators have found that drinking tests are a less sensitive predictor of impaired accommodation or visceral hypersensitivity than the barostat study [13]. No data are available on the usefulness of drinking tests in comparison with the gold standard method, the barostat, in Japan.…”
Section: Introductionmentioning
confidence: 99%